INVESTIGATION OF ORGANOMETAL HALIDE PEROVSKITE CRYSTAL LAYER PREPARATION FOR HIGH EFFICIENCY SOLAR CELLS - ASMA NURUNNIZAR (NIM: 20215005), ADHITA
Solar cells based on organometal halide perovskite materials are a class of an emerging new type of solar cell that is most intensively studied in recent years. This fact is related to the unique properties and advantages of the organometal halide perovskite materials as the active layer of this type of solar cell, namely a small direct band gap, high light absorption coefficient, and good carrier transport properties. Moreover, thin layer of this perovskite materials can be fabricated through a solution-process so that it can be prepared without requiring a vacuum chamber. The perovskite solar cell structure studied in this thesis has an FTO/c-TiO2/mp-TiO2/MAPbI3/HTL/Au structure, where HTL is a hole transport layer. The preparation method for the perovskite layer is a one-step precursor deposition (OSPD). After the fabrication into a solar cell, it will be characterized by various methods such as Scanning Electron Microscopy (SEM), X-Ray Difractometry (XRD) and photovoltaic characteristics (I-V) measurements. Preparation of perovskite layers with various fabrication parameters have been carried out in order to obtain a good perovskite layer, which has the desired crystal structure and uniform morphology. The SEM images show that the perovskite layers show various morphologies depending on the process parameters. Some samples looks like a resemble of random needle-like shapes or overlapping webbing, while other samples looks like a resemble of flake-like shapes or islands. It can also be seen easily the presence of the areas on the layer that are not covered by the perovskite layer. Poor perovskite layer visually looks like a greyish black color, so that its absorption spectrum broadens up to the near infra-red region (about 1100 nm). Under a particular preparation condition and process, a perovskite layer showing islands-like morphology with about 300 nm - 900 nm in size and separated by a very narrow gap of about 12 nm -22 nm was eventually formed. This perovskite layer shows dark brown, which corresponding to the cut off of light absorption spectrum at about 780 nm. Solar cells with this kind characteristics of perovskite layer produces a short-circuited photocurrent density (Jsc) of about 18,4 mA/cm2 and power conversion efficiency (PCE) of about 7,0 %. Currently, the fill factor parameter was still small because there are still interfacial junction problems.